PENGARUH PENDEKATAN KONTEKSTUAL TERHADAP HASIL BELAJAR SISWA DALAM MATERI MENGENAL ALAT MUSIK MELODIS - Ningrum, Nurasih Setya; Julia, Julia; Irawati, Riana (Jurnal Pena Ilmiah, 2017)
The purpose ofi this research is to know the effect of the contextual approach in improving student learning results on materials familiar with melodic instruments, as well as to know differences in student learning results using contextual approaches and conventional approaches in classroom students IV SDN Sukalilah. The method usedlin this research is anexperimentalimethodkwith pretestoposttestpcontrolpgroup design. Theppopulation in this researchmismthelfourth graders of elementary school in Pamulihan sub-district. While for the sample is the students of grade IVB SDN Sukalilah as experimentaliclass andlstudentslof class IVApSDNlSukalilah aska controloclass. The instrument used is a matter of student learning results with materials familiar with melodic instruments, observation, and interview. Result of research with significant level Î± = 0,05 indicate that learning with contextual approach can improve student learning result significantly than conventional learning.